2013
DOI: 10.1002/hep.26069
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic Effects of the Chemokine, CXCL 10 Are Mediated by the Noncognate Receptor TLR4 in Hepatocytes

Abstract: Aberrant expression of the chemokine CXC chemokine ligand (CXCL)10 has been linked to the severity of hepatitis C virus (HCV)-induced liver injury, but the underlying molecular mechanisms remain unclear. In this study, we describe a yet-unknown proapoptotic effect of CXCL10 in hepatocytes, which is not mediated through its cognate chemokine receptor, but the lipopolysaccharide receptor Toll-like receptor 4 (TLR4). To this end, we investigated the link of CXCL10 expression with apoptosis in HCV-infected patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 37 publications
3
47
1
1
Order By: Relevance
“…In vitro studies have shown that liver resident cells (e.g. hepatocytes, Kupffer cells, hepatic stellate cells) express these chemokines as a response to cellular injury and stress [20][21][22][23][24][25], suggesting a hepatic release of these chemokines. However, it was also implicated that circulating immune cells might contribute to elevated chemokine levels [23,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown that liver resident cells (e.g. hepatocytes, Kupffer cells, hepatic stellate cells) express these chemokines as a response to cellular injury and stress [20][21][22][23][24][25], suggesting a hepatic release of these chemokines. However, it was also implicated that circulating immune cells might contribute to elevated chemokine levels [23,29].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CXCR3 ligands, especially CXCL9, are increased during liver diseases [5][6][7][8][9][10][11][12] and are functionally linked to hepatic injury, inflammation, fibrosis, [8][9][10][12][13][14][15][16][17][18], angiogenesis [6] and complications of cirrhosis [19]. Liver resident cells, such as hepatocytes, Kupffer cells and hepatic stellate cells were found to represent a major source of CXCR3 ligands in the liver [20][21][22][23][24][25]. The increased intrahepatic levels of CXCR3 ligands during liver disease are also paralleled by elevated serum levels, as demonstrated in various animal and human studies [8,11,13,14,[16][17][18][19][26][27][28].…”
Section: Introductionmentioning
confidence: 98%
“…Up-regulation of type III IFN, IL-28 and IL-29 mRNA were detected in liver and increased levels of IL-28 and IL-29 protein in serum of chimpanzees with acute HCV infection [20, 21]. RIG-I, TLR3, and TLR7, and induce interferons, cytokines, and chemokines during HCV infection [36, 37]. RIG-I mediated IFN response was shown to play an important role in controlling virus infection in HCV-infected cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that CXCL10 expression correlates with the degree of apoptosis in patients with hepatitis C and that this action is mediated by activation of the noncognate receptor TLR-4. 42 Intrahepatic and even serum CXCL10 levels have been reproducibly associated with the extent of HCV-induced liver fibrosis. [43][44][45][46][47] Circulating CXCL10 is also an independent biomarker for the recurrence of significant fibrosis after liver transplantation in HCV-infected patients.…”
Section: Viral Hepatitismentioning
confidence: 99%